2017
DOI: 10.2196/publichealth.6796
|View full text |Cite
|
Sign up to set email alerts
|

Twitter and Public Health (Part 2): Qualitative Analysis of How Individual Health Professionals Outside Organizations Use Microblogging to Promote and Disseminate Health-Related Information

Abstract: BackgroundTwitter is the most popular form of microblogging that is being utilized in public health to engage audiences and to communicate health-related information. Although there is some research showing the various forms of Twitter use in public health, little is known about how individual public health professionals are using their personal Twitter accounts to disseminate health information.ObjectiveThe purpose of this research was to categorize public health professionals’ tweets to evaluate how individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…We employed a two-phased thematic analysis to identify the types of content health care institutions post on their institutionally sponsored Facebook pages. Thematic analysis is a qualitative method used to identify, analyze, and report on patterns found in text data [ 14 - 16 ]. Use of the method requires “careful reading and rereading of the data” [ 17 ] to identify explicit and implicit meaning embedded within the text [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…We employed a two-phased thematic analysis to identify the types of content health care institutions post on their institutionally sponsored Facebook pages. Thematic analysis is a qualitative method used to identify, analyze, and report on patterns found in text data [ 14 - 16 ]. Use of the method requires “careful reading and rereading of the data” [ 17 ] to identify explicit and implicit meaning embedded within the text [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…In a study on social media sharing of public health professionals, the terms "public health practitioner", "MPH" (masters in public health), "public health" and "APHA" (American Public Health Association) were chosen. At the end of the study, it has been shown that public health professionals were sharing tweets to combat misinformation about Ebola (Hart et al, 2017). The use of social media is also a new tool for health organisations to share health-related information (Twynstra and Dworatzek, 2015).…”
Section: Images and Contentmentioning
confidence: 99%
“…Thematic analysis is a qualitative method used to identify, analyze, and report on patterns found in text data [14][15][16]. Use of the method requires "careful reading and re-reading of the data" [17] (p. 258) to identify explicit and implicit meaning embedded within the text.…”
Section: Overviewmentioning
confidence: 99%